Determinants of job stress among fast food employees in Klang Valley, Malaysia - Ghazali, Hazrina; Ying, Chng Yee; Dato’ Mansor, Zuraina; Othman, Mohd Amar Ridham (RSIS International, 2024)
The booming of fast-food industry in Malaysia has led to a concerning increase in job stress among fast- food employees. Hence, the purpose of this study was to identify the key determinants of job stress and its impact on fast-food workplaces. In this study, four variables were used: working environment, job insecurity, person-organization fit, and compensation and benefits. The study was conducted in fast-food restaurants in the Klang Valley area. The primary data for this study was collected through quantitative approach from fast-food employees. A total of 210 sets of self-administered questionnaires was distributed and 201 sets of questionnaires were valid with 95.7% of response. After that, all the data was analyzed through Statistical Package for the Social Sciences (SPSS) version 27. The result found that the working environment was the most influential factor contributing to job stress. Results also showed that 72.7% of respondents, perceived high levels of stress in the fast-food restaurants. It was expected that findings from this study could suggest the organizations’ top management to highlight factors that could contribute to job stress and strategize ways to overcome employees’ job stress in the long run.